2013
DOI: 10.1097/nmd.0b013e31827f636d
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Mental Illness and Risk for Developing a New Disorder After Hurricane Katrina

Abstract: To investigate predisaster mental illness as a risk factor of poor postdisaster mental health outcomes, veterans with (n = 249) and without (n = 250) preexisting mental illness residing in the Gulf Coast during Hurricane Katrina were surveyed after Katrina and screened for posttraumatic stress disorder (PTSD), depression, generalized anxiety disorder, and panic. Logistic regression examined the association between preexisting mental disorders and positive screens after the hurricane, adjusting for demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…First, most were cross-sectional and unable to examine GxE at different time points post-disaster. Second, all lacked pre-disaster data, even though prior studies have shown that pre-disaster factors (e.g., mental health status, degree of social support) are among the strongest predictors of post-disaster psychological responses (Ginexi et al, 2000, Norris et al, 2002, Sullivan et al, 2013). As a result, it remains unclear to what extent GxE predicts psychopathology beyond pre-disaster factors.…”
Section: Introductionmentioning
confidence: 99%
“…First, most were cross-sectional and unable to examine GxE at different time points post-disaster. Second, all lacked pre-disaster data, even though prior studies have shown that pre-disaster factors (e.g., mental health status, degree of social support) are among the strongest predictors of post-disaster psychological responses (Ginexi et al, 2000, Norris et al, 2002, Sullivan et al, 2013). As a result, it remains unclear to what extent GxE predicts psychopathology beyond pre-disaster factors.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, this has been achieved by comparing those exposed to disaster with similar population groups not exposed, [8][9][10] whereas in other cases, time series comparisons have been made of outcomes assessed before and after the disaster. [11][12][13][14][15][16][17] Both methods have limitations and, under ideal circumstances, it would be desirable to assess the outcomes of those exposed to the disaster with the outcomes of a comparison group, with both groups being assessed both before and after the disaster.…”
mentioning
confidence: 99%
“…A number of studies have assessed mental health problems using either measures of symptoms 8,11,16 or changes in substance consumption, 15,17,18 whereas others have used categorical measures of meeting criteria for DSM disorders. 10,[12][13][14] There is a growing literature that suggests it is important to assess both categorical and dimensional aspects of mental disorders particularly as there may be individuals who display symptoms of disorder (including impairment) and experience significant distress but whose symptoms do not meet diagnostic criteria. [25][26][27][28] These developments are reflected by the inclusion of dimensional aspects in the assessment of mental disorders in the DSM-5.…”
mentioning
confidence: 99%
“…13,14 Similarly, researchers have largely relied on retrospective self-reports on pre-disaster psychopathology. 6,7 There are a few exceptions, [15][16][17] and they generally show that pre-existing psychopathology influences post-disaster mental health. Thus, it awaits to be firmly established the extent to which disasters induce lasting risks of severe psychiatric disorders independently of underlying vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%